Pengaruh Kompetensi, Kecerdasan Emosional Dan Budaya Kerja Terhadap Kinerja Pegawai Badan Pengelolaan Keuangan, Pendapatan Dan Aset - Robertho Duran Situmorang; Thamrin Sihombing; Muhammad Raja Inal Siregar; Musjamiri; Wawan Samudra; Supriadi; Ismail Nasution (Forum Kerjasama Pendidikan Tinggi, 2023)
Problem of this study what is influence of competency on performance. What is influence of emotional intellegence on performance. What is influence of job culture on performance. What is influence competency, emotional intellegence and job culture on performance. The purpose of this study to determine and analyze the effect of competency on performance. Determine and analyze the effect of emotional intellegence on performance. Determine and analyze the effect of job culture on performance. Determine and analyze the effect of competency, emotional intellegence and job culture on performance. Sample in the study is 54 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate competency has a positive and significant effect on performance. Emotional intellegence has a positive and significant effect on performance. Job culture has a positive and significant effect on performance. Competency, emotional intellegence and job culture has a positive and significant effect on performance.